Carbon fixation and rhodopsin systems in microbial mats from hypersaline lakes Brava and Tebenquiche, Salar de Atacama, Chile - Kurth, Daniel German (2021)
In this work, molecular diversity of two hypersaline microbial mats was compared by Whole Genome Shotgun (WGS) sequencing of environmental DNA from the mats. Brava and Tebenquiche are lakes in the Salar de Atacama, Chile, where microbial communities are growing in extreme conditions, including high salinity, high solar irradiance, and high levels of toxic metals and metaloids. Evaporation creates hypersaline conditions in these lakes and mineral precipitation is a characteristic geomicrobiological feature of these benthic ecosystems. The mat from Brava was more rich and diverse, with a higher number of different taxa and with species more evenly distributed. At the phylum level, Proteobacteria, Cyanobacteria, Chloroflexi, Bacteroidetes and Firmicutes were the most abundant, including ~75% of total sequences. At the genus level, the most abundant sequences were affilitated to anoxygenic phototropic and cyanobacterial genera. In Tebenquiche mats, Proteobacteria and Bacteroidetes covered ~70% of the sequences, and 13% of the sequences were affiliated to Salinibacter genus, thus addressing the lower diversity. Regardless of the differences at the taxonomic level, functionally the two mats were similar. Thus, similar roles could be fulfilled by different organisms. Carbon fixation through the Wood-Ljungdahl pathway was well represented in these datasets, and also in other mats from Andean lakes. In spite of presenting less taxonomic diversity, Tebenquiche mats showed increased abundance and variety of rhodopsin genes. Comparison with other metagenomes allowed identifying xantorhodopsins as hallmark genes not only from Brava and Tebenquiche mats, but also for other mats developing at high altitudes in similar environmental conditions.